Discarded fish on the Spanish Mediterranean coast: influence of season on fatty acids profiles - SUÁREZ, MARÍA DOLORES; SÁEZ, MARÍA ISABEL; RINCÓN-CERVERA, MIGUEL ÁNGEL; HIDALGO, LUIS; GUIL-GUERRERO, JOSE LUIS (Mediterranean Marine Science, 2021)
This work focused on determining the fatty acid (FA) composition of commonly discarded fish on the Spanish Mediterranean coast in winter and summer to assess their potential use as raw sources of very long-chain polyunsaturated fatty acids (VLCPUFAs). Total n-3 VLCPUFA content significantly varies depending on capture season, and values were higher in winter for Pomadasys incisus (1.36 g/100 g), Chelidonichthys lucerna (1.67 g/100 g) and Trachinus draco (2.04 g/100 g), while Pagellus acarne had larger n-3 PUFA amounts in summer (3.89 g/100 g). Generally for most species, monounsaturated FA, eicosapentaenoic acid (20:5n-3) and total FA had higher values in summer, while both the n-3 VLCPUFA fraction and DHA content were higher in winter. Knowledge of these changes allows the processes for their proper use as valuable PUFA sources to be adjusted. The discarded fish herein studied could be generally considered to be raw n-3 VLCPUFAs sources.